Ka-band beacon receiver and telecommunication link study - Boo, Chin Boon. (2009)
The demand for space services frequencies in the Asia region has increased rapidly and higher frequency bands like Ka-band (30/20 GHz) have been used to relieve the congestion. However, higher frequencies are susceptible to higher rain attenuation especially in the tropical region. Hence, assessment of the effects of rain on the operation of these frequency bands satellite services in Singapore was done to characterize rainfall rate and rain attenuation. Polarization is also research on in the literature review. The scope of the project is to study the correlation between rainfall rate and the Ka-band satellite beacon signal attenuation. The Ka-band satellite dish looking at IPSTAR satellite was shifted to look at WINDS satellite while the beacon receiver system on S2 roof-top of Nanyang Technological University (NTU) is used to receive data. Modifications were made to the beacon receiver in order to ensure accuracy of the data collection with the support from James Cook University (JCU). Weather stations and the Ka-band rain gauge were installed beside the satellite dish to measure the rainfall rate. Finally, software such as Microsoft Excel and Matlab were used to extract and analyze the data. This report explains the hardware aspects of the beacon receiver system in depth and the weather stations installed. Link budgets were computed to determine the dynamic range of the downlink beacon receiver systems. The method for aligning the beacon receiver dish to the satellite was also documented. Lastly, this report illustrates the analysis between rainfall rate and signal strength for the Ka band and was then compared with the results from the Ku band.